Proceedings of 2013 4th International Asia Conference on Industrial Engineering and Management Innovation (IEMI2013) - Qi, Ershi; Shen, Jiang; Dou, Runliang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The purpose of the 4th International Asia Conference on Industrial Engineering and Management Innovation (IEMI 2013) is to bring together researchers, engineers and practitioners interested in the application of informatics to usher in new advances in the industrial engineering and management fields.
Advanced design and manufacturing -- Decision Analysis/Decision Support System -- Lean manufacturing -- Logistics Engineering and Supply Chain Management -- Operations Research -- Production Planning and Control -- System Modeling and Simulation -- Author Index.
Keywords: Economics; Engineering; Industrial engineering; Engineering economy; Economics/Management Science; Innovation/Technology Management; Engineering Economics, Organization, Logistics, Marketing; Industrial and Production Engineering; Engineering, general